Access to and use of health and social services among people who inject drugs in two urban areas of Mozambique, 2014: qualitative results from a formative assessment - Liliana Dengo-Baloi; Makini Boothe; Cynthia Semá Baltazar; Isabel Sathane; Denise Chitsondzo Langa; Manuel Condula; Helena Ricardo; Celso Inguane; Eugénia Teodoro; Lídia Gouveia; Henry F. Raymond; Roberta Horth (BMC, 2020)
Abstract Background Prior to 2014, data about health seeking behaviors or service uptake for People who inject drugs (PWID) in Mozambique did not exist. We present the results from the formative assessment component of the Biological and Behavioral Survey (BBS). Methods Standardized interview guides were used during key informant interviews (KII) and focus group discussions (FGD) in Maputo and Nampula/Nacala to discuss issues related to risk behaviors and access to and utilization of health and social services by PWID. The target sample size was not defined a priori, but instead KII and FGD were conducted until responses reached saturation. Data analysis was based on the principles of grounded theory related to qualitative research. Results Eighty-eight respondents, ages 15 to 60, participated in KIIs and FGDs. Participants were majority male from diverse income and education levels and included current and former PWID, non-injection drug users, health and social service providers, peer educators, and community health workers. Respondents reported that PWID engage in high-risk behaviors such as needle and syringe sharing, exchange of sex for drugs or money, and low condom use. According to participants, PWID would rather rent, share or borrow injection equipment at shooting galleries than purchase them due to stigma, fear of criminalization, transportation and purchase costs, restricted pharmacy hours, personal preference for needle sharing, and immediacy of drug need. Barriers to access and utilization of health and social services include distance, the limited availability of programs for PWID, lack of knowledge of the few programs that exist, concerns about the quality of care provided by health providers, lack of readiness as a result of addiction and perceived stigma related to the use of mental health services offering treatment to PWID. Conclusions Mozambique urgently needs to establish specialized harm reduction programs for PWID and improve awareness of available resources. Services should be located in hot spot areas to address issues related to distance, transportation and the planning required for safe injection. Specific attention should go to the creation of PWID-focused health and social services outside of state-sponsored psychiatric treatment centers.